Pemberdayaan Calon Instruktur Dalam Memahami Materi Skema Associate Data Scientist - Siswanto; Riefky Sungkar; Muhammad Anif; Ari Saputro; Subandi; Djati Kusdiarto; Wahyu Pramusinto; Hari Prasetyo, Basuki (Ikatan Ahli Informatika Indonesia, 2023)
At the Information & Communication Technology Training & Development Center (BPPTIK) Cikarang, Bekasi Regency, West Java, community service (PKM) was performed. BPPTIK is responsible for conducting competency assessments, certifying and accrediting government training facilities, and providing information and communication technology product services. The current issues facing PKM partners are as follows: teachers who are part of BPPTIK are now lacking in trainers to impart associate data scientist scheme material based on SKKNI, which includes knowledge, abilities, and attitudes. The goal of this training is to prepare aspiring instructors who are BPPTIK Cikarang members with the knowledge, abilities, and attitudes of the SKKNI-based associate data scientist scheme material so that instructors can deliver descriptions, curriculum, syllabus, teaching materials, and modules. In the UAT test, a questionnaire with a Likert scale of 5 has been used. As a result, the respondents agreed (above 79.24%) that overall the SKKNI-based associate data scientist scheme material training is interesting and understood by prospective associate data scientist instructors who are members of BPPTIK Cikarang.